Peran Komunikasi Efektif Dalam Membangun Hubungan Guru-Anak Usia Dini Yang Bermakna - Rotua Simanjuntak; Elisa Simatupang; Imma Niani Gulo; Aman Simare-mare; Elya Siska Anggraini (Journal Innovation In Education, 2024)
Effective communication between teachers and early childhood children plays an important role in forming significant and meaningful relationships. In this article, the author discusses the role of effective communication in building meaningful teacher-early childhood relationships. This research uses a qualitative approach with case study methods and analysis of symbolic interaction theory. The research results show that effective communication between teachers and young children requires the characteristics of teachers who are patient, willing to make sacrifices, attentive, firm, and able to attract the attention of young children. In addition, teachers must understand the diverse characters of their students and use effective media to achieve meaningful communication. Thus, effective communication can help in developing early childhood social skills, improving the quality of intrapersonal relationships, and avoiding conflict. Therefore, it is important to stimulate effective communication in children from an early age to build meaningful relationships between teachers and young children.